Membangun Kerjasama Tim yang Efekti dalam Organisasi - Aida Lasmi; Habib Bayhaqi; Suhairi Suhairi (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Team building is a group of individuals who have a common goal to be achieved. And to achieve this goal, good cooperation is needed, sharing feelings, mutual respect and mutual encouragement among group members. Several things that affect the formation of groups, among others, are the existence of communication, motivation, being able to manage conflict, competition and cooperation. Cooperation is a means and a sign related to the quality of the group as a gathering place for people in an organization. In building group cooperation, mutual trust, openness or transparency, self-realization or self-realization and interdependence are needed.